2017
DOI: 10.4103/jrpp.jrpp_17_16
|View full text |Cite
|
Sign up to set email alerts
|

An interprofessional collaboration between medicine and pharmacy schools: Designing and evaluating a teaching program on practical prescribing

Abstract: Objective:Medical students need proper education in drug prescription. The aim of the present study is to introduce a course that improves the students' prescribing skills and also promotes an interprofessional collaboration between medicine and pharmacy schools.Methods:This study was done in a skill laboratory at the pharmacotherapy department of Tehran University of Medical Sciences, Tehran, Iran. The course was an 18-h interactive workshop in 3 days under the supervision of clinical pharmacists. A total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…The apparent decrease in skills in the control group (NTG) was concerning and potentially a result of inconsistent prescribing-specific experiential teaching and learning. Previous studies have demonstrated that instilling poor skills and habits amongst medical students early in their clinical development is avoidable with appropriate training by informed educators ( 18 , 19 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The apparent decrease in skills in the control group (NTG) was concerning and potentially a result of inconsistent prescribing-specific experiential teaching and learning. Previous studies have demonstrated that instilling poor skills and habits amongst medical students early in their clinical development is avoidable with appropriate training by informed educators ( 18 , 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Comparing educators was not the purpose of this study. However, a number of articles have demonstrated pharmacists have a positive influence on prescribing behaviours of prescribers ( 18 , 19 , 21 , 22 ). Given that all students, except one, received this education from a prescribing physician it is unlikely to represent a confounder to our findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was a mix of study designs, including eight randomised controlled trials [20][21][22][23][24][25][26][27], nine comparative studies [28][29][30][31][32][33][34][35][36], six prospective studies [37][38][39][40][41][42], 12 before and after studies [43][44][45][46][47][48][49][50][51][52][53][54], five mixed-method evaluation studies [55][56][57][58][59], five crossover studies [60][61][62][63][64], five quasiexperimental studies [65][66][67][68][69] and four cross-sec...…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Regardless, both statistics identify illiteracy as a major obstacle for the delivery of self-management coaching to older adults. This obstacle could explain the dearth of educational interventions; there was only one interventional study that suggested the effectiveness of an educational program on reducing insulin-pen medical errors (Javadi, Khezrian, Sadeghi, Hajimiri, & Eslami, 2017).…”
Section: Interactive Educational Programs That Improve Self-managemenmentioning
confidence: 99%